POWER OF PARDON IN THE SHARĪ‘AH AND ITS APPLICABILITY IN COMMON LAW - Uddin, Moin; Faruqi, Shad Saleem (Jurnal Syariah, 2024)
The power of pardon is an important principle for umholding justice in the criminal justice systems of both common law and the Sharīʿah. The Sharīʿah pardon principle provides a fair opportunity for the victims or victims’ heirs in murder cases to express their preferences as to how the offenders should be pardoned, and while also ensuring the perpetrators’ rights as both disputing parties have to participate in the pardon process actively. However, the Sharīʿah pardon principle has certain inadequacies compared to the common law pardon process that hinder its independent implementation in the existing common law pardon process. The current common law pardon process can also be considered arbitrary and one-sided compared to the Sharīʿah pardon principle because the pardon petitions are decided exclusively by the state authorities, and victims or victims’ heirs in murder cases are not heard or compensated. Therefore, this study aims to examine the Sharīʿah pardon principle and explore its potential to enhance justice in the common law pardon decision-making process. This study utilises a qualitative doctrinal method depending on the requirements for pardon as outlined in cases of qiṣāṣ. Primary attention is given to the relevant Qur’ānic verses, the Sunnah and a review of the juristic opinions on the extent of the application of these rules. This study submits that the common law pardon process can be improved if it is harmonised with the Sharīʿah pardon principle. This article further suggests how this harmonisation effort can be realised to develop an implementable and balanced pardon decision-making process that can enhance justice in common law jurisdictions.